Driving fatigue in professional driver (e-hailing) - Shazwana, Omar (2025)
Fatigue among e-hailing drivers has emerged as a critical issue due to its implications for driver well-being and road safety. This study investigates the occupational factors influencing fatigue frequency and its impact on e-hailing drivers' performance. A total of 60 respondents were surveyed, representing a cross-section of e-hailing drivers, with data collected through structured questionnaires. The study explores key demographic, occupational, and accident-related factors to determine their association with fatigue. The findings reveal that prolonged work hours, inadequate sleep, prolonged driving hours, and insufficient breaks significantly contribute to fatigue among drivers. Specifically, 58.3% of respondents reported sleeping less than six hours daily, and 33.3% experienced fatigue "very often." Fatigue was also identified as a contributing factor in 26.7% of accidents reported within the past 12 months. This study emphasizes the urgent need for interventions to mitigate fatigue among ehailing drivers. Recommendations include implementing rest policies, encouraging regular breaks, leveraging fatigue-monitoring technologies, and providing education on fatigue management. Despite a smaller sample size than initially targeted, the study provides valuable insights and lays the groundwork for future research. By addressing fatigue-related challenges, e-hailing companies can enhance driver safety and contribute to safer road environments.